Сучасні аспекти лікування низькорослості у дітей з передчасним статевим дозріванням - Bolshova, O.V.; Samson, O.Ya.; Sprynchuk, N.A.; Derevianko, D.I.; Derevianko, G.A. (Ендокринологія | Endokrynologia, 2011)
Сучасні аспекти лікування низькорослості у дітей з передчасним статевим дозріванням